Transcatheter closure of secundum atrial septal defects with the atrial septal defect occlusion system (ASDOS): initial experience in children. - Hausdorf, G. (1996)
OBJECTIVE--To report initial experiences with transcatheter occlusion of atrial septal defects using a new occlusion device. SUBJECTS--10 children aged 1.1 to 14.9 years. INCLUSION CRITERIA--Patients with a body weight above 10 kg, normal pulmonary resistance and an indication for surgical closure of a secundum atrial septal defect, a residual tissue rim of interatrial septum surrounding the defect of more than 5 mm, and a maximum defect diameter of 20 mm. METHODS--The defects were closed by a transcatheter device (ASDOS) consisting of two umbrellas which are introduced over a guidewire loop. Both umbrellas consist of a central body and five arms formed from preshaped nitinol wire covered with a thin polyurethane patch. The central body of the distal umbrella contains a thread, the proximal umbrella contains a bolt. The two umbrellas are connected by screwing the bolt on the thread using a screwdriver catheter. RESULTS--The implantation was performed under echocardiographic guidance; in six of 10 patients, transoesophageal echocardiography was necessary. The "stretched" diameter of the defect evaluated during balloon sizing ranged from 10 to 20 mm, and the pulmonary to systemic blood flow ratio from 1.5:1 to 2.8:1. Transcatheter closure was successfully performed in 9/10 patients using devices with a diameter of 25 mm to 40 mm. No severe complications occurred. However, in one patient with a pre-existing prolonged PR interval brief periods of second and third degree atrioventricular block occurred after the implantation but normalised within 3 d. During a follow up period of 21 to 29 weeks no device embolisation, thromboembolic complications, fractures of the implanted device, atrial perforations, pericardial effusions, obstructions of systemic or pulmonary veins, atrioventricular valve dysfunction, or other complications occurred. CONCLUSIONS--The new device is a promising transcatheter approach for the occlusion of secundum atrial septal defects in children. However, further evaluation and long term data are needed before this transcatheter technique can be recommended.